KOMPOSISI MIKROORGANISME PADA BEBERAPA DEPOT AIR MINUM ISI ULANG DI KOTA MANADO [Composition Microorganisms In Some Water Depot Refill in Manado City] - Watung, Agnes T.; Sembel, Dantje T.; Ijong, Frans G. (Pascasarjana Unsrat, 2014)
Drinking Water Refill (AMIU) the price is relatively cheaper, but not all drinking water refill depot in the city of Manado guaranteed security products. This is because there are many depot refill drinking water that has not been officially registered in the Ministry of Trade and Industry, only 20 of 130 registered depot depot there and have not been routinely tested water quality. This study analyzes the goal of microorganisms on a depot refill drinking water, water tank transporters and the source of raw water in the city of Manado which include, pH, temperature, total plate number, E.coli and yeast to get a refill drinking water quality that meets the requirements .Â The results for total plate count 13 depots (39%), 1 tank (20%), there are three sources of raw water (27%) who do not meet the requirements, the total coliform in the depot there are 19 (58%), water tank transporter 3 (60%) of raw water sources there were 6 (55%) who do not meet the requirements, there are 8 depot E. coli (24%), water tank transporter 1 (20%), source of raw water 7 (64%) who do not meet the requirements, for mushrooms in the depot <10 while on the tank and raw water sources ranged from <10 - > 300 and pH at all sample points in both depots, tank and all water sources to meet the requirements, for the temperature at the depot, there were 12 (36%), the tank 1 (20%), 3 raw water sources (27%) who do not meet the requirements. Results of this study concluded that the quality of drinking water in the depot, tank and raw water sources, there are still 60.20% - 67.35% which is satisfactory from a microorganism, and for the physical parameters of temperature are 67.35Â Â % while meeting the requirements of the chemical parameters pH 100% compliant.